An investigation of risk factors for two successive cases of clinical mastitis in the same lactation - Pantoja, J. C.F. [UNESP]; Almeida, A. P. [UNESP]; dos Santos, B. [UNESP]; Rossi, R. S. [UNESP] (Elsevier, 2016)
The objective of this study was to identify risk factors for the occurrence of two successive cases of clinical mastitis (CM). Two farms were visited monthly during 10 months. Milk samples were collected from all cases of CM that occurred during the study. Cows were observed prospectively from the beginning of the study and a case cow was defined when she experienced the second case of CM within the same lactation. For each case cow, 3 control cows matched by days in milk (DIM) were randomly selected from the cohort of cows who did not experience CM. On each visit day, a series of udder and teat characteristics were recorded during milking time: teat-end hyperkeratosis scoring, milking ease scoring, teat length and diameter, teat-to-ground distance, and udder position in relation to the hock. A total of 113 case cows and 324 control cows were used for analyses. The median time to occurrence of the first case of CM was 84 DIM and the median interval between the first and second cases of CM was 39 days. Of all second cases, 49.6% (N=55) occurred in the same mammary gland. Of these 55 cases, 29.1% had identical milk culture results from both first and second cases. Most cases of CM were caused by coliforms and environmental streptococci. Teat-to-ground distance, teat-end hyperkeratosis, udder position in relation to the hock, milking ease, parity, and milk production at the first test of lactation were individually associated with the occurrence of two successive cases of CM. Of all explanatory variables, 3 remained in the final multivariable model. The odds of two successive cases of CM were 3.7 times greater for cows who were “very easy to milk”, as compared with cows who were “difficult to milk”. Cows who had their udders below the hock, and those of parity >2 were 3.6 and 2.5 times more likely to experience two successive cases of CM, as compared with cows whose udder was positioned above the hock, and cows of parity 1, respectively. Findings of this study highlight the importance of teat and udder characteristics as risk factors for two successive cases of CM. Further investigations are needed to elucidate the role of the teat canal in preventing mastitis for modern cows that have been selected for increased milk production, shorter teats, and greater milk flow rates.
Keywords: Clinical mastitis; Dairy cows; Epidemiology; Milk quality; Milking ease; Teat-end hyperkeratosis